PENGARUH PENERAPAN PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD PENGADAAN BARANG DAN IMPLIKASINYA PADA KINERJA KEUANGAN ( Studi pada Rumah Sakit Pemerintah dan Swasta di Kota Bandung ) - Eka Ariaty Arfah (InFestasi, 2011)
The aim of this study is to analysis the effect of internal control applying on good levying fraud prevention and its implication to the financial performance. Survey the sum of 105 responder covering hospital directors, financial director, accounting/finance chief, staff of general section, financial section and supply section on the public and private hospital in Bandung city. Data have been collected by questioner and hospital financial reports. The tools of statistic analysis using multiple regression.The result of this study indicates that there is positive effect of internal control applying on good levying fraud prevention and its implication to the financial performance. Its means that financial performance influenced by internal control applying on good levying fraud prevention and influenced residue by other factors are not included in this study model.